1983
DOI: 10.1128/iai.42.2.696-700.1983
|View full text |Cite
|
Sign up to set email alerts
|

Purification and immunochemical characterization of Streptococcus sanguis ATCC 10557 serotype II carbohydrate antigen

Abstract: Cell wall carbohydrate antigen of Streptococcus sanguis ATCC 10557 (serotype II/biotype B) was extracted from purified cell walls by treatment with 5% trichloroacetic acid at 4°C for 8 h. The extract was purified by chromatography on DEAE-Sephadex A-25 and Sephadex G-100 columns. The purified carbohydrate antigen produced a single precipitin band against anti-type II serum, which fused with the band produced by the autoclaved extract or the phenol-water extract of the S. sanguis cells. The type II antigen was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…In addition to epitopes that do not include the Gn or G motifs, other epitopes may overlap with these regions as suggested by the demonstration of cross-reactivity between the 2G and 3G polysaccharides. A possible structural basis for these cross-reactions is suggested by the previous identification of GalNAc as the immunodominant sugar of the 3G polysaccharide, a molecule designated as the serotype II carbohydrate in earlier studies (22,38). Significantly, the only GalNAc unit in the 3G structure is GalNAc␣ in the G motif ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…In addition to epitopes that do not include the Gn or G motifs, other epitopes may overlap with these regions as suggested by the demonstration of cross-reactivity between the 2G and 3G polysaccharides. A possible structural basis for these cross-reactions is suggested by the previous identification of GalNAc as the immunodominant sugar of the 3G polysaccharide, a molecule designated as the serotype II carbohydrate in earlier studies (22,38). Significantly, the only GalNAc unit in the 3G structure is GalNAc␣ in the G motif ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…Results from previous studies of the 10557 polysaccharide suggested that GalNAc was an immunodeterminant (Koga et al, 1983); however, this proposal was based on the inhibition of immunoprecipitation by a very high concentration of the monosaccharide. Further studies with oligosaccharide fragments of these polysaccharides are in progress to firmly establish their respective antigenic and receptor regions.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to a calibrated column of Sephacryl S-400 (Pharmacia) in a 0.1 M NaCl, 0.01 M Tris HC1 buffer (pH 7.6), the 10557 polysaccharide emerged at a position similar to that of a clinical dextran (Sigma D4751) with average molecular mass of 80 kDa determined by light scattering. The 10557 polysaccharide gave a reaction of complete identity with a sample of the previously studied ATCC 10557 serotype II carbohydrate antigen (Koga et al, 1983) kindly provided by Dr. S. Hamada (Osaka University, Suita-Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodiffusion was performed in 1% (wt/vol) Noble agar (Difco) in saline (13). Quantitative precipitin reaction and hapten inhibition tests were performed as previously described (13). Monosaccharides and the partial hydrolysate of the purified antigen were used as haptens.…”
Section: Methodsmentioning
confidence: 99%